EFFORTS IN DEFENDING THE EXISTENCE OF WOMEN WITH DISABILITIES - Ratnawati,; Putra, A. Reindera (International Journal of Psychosocial Rehabilitation, 2020)
The stereotypes occurance of women with disabilities makes tehir existence increasingly marginalized, especially in social society. This has led the emergence of Non-Governmental Organizations (NGOs) that strive to defend the existence of women with disabilities. Therefore, the focus of this research problem is "how are NGOs trying to defend the existence of women with disabilities? Using a case study on the NGO of Sentra Advokasi Perempuan Difabel, dan Anak (SAPDA) Yogyakarta or Advocacy Center for Disabled Women and Children, the results of this study conclude that the efforts made by SAPDA in defending their existence in Yogyakarta use issues of quality of life and human rights values, mobilize public opinion with a broad scale of the movement and the actors involved are those from the middle class..